EDUKASI TUGAS DAN WEWENANG POLRI DALAM MENANGGULANGI TINDAK PIDANA PENCABULAN - Migi Saputra Jaya, Dwikari Nuristiningsih, Andri Zulpan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study discusses the role and authority of the Indonesian National Police in tackling acts of molestation in the jurisdiction of Kaur Police Department. The research uses a socio-legal and case study approach. The study shows that the Kaur Police implement three main strategies: pre-emptive, preventive, and repressive, in accordance with Law Number 2 of 2002. Obstacles faced include internal (personnel and budget), external (patriarchy and low legal awareness), technical (sectoral coordination), and legal (weak regulations and court decisions). Strengthening synergy among law enforcement, government, and the community is key to improving victim protection and crime prevention.